КОНЦЕПТУАЛЬНІ ОСНОВИ ВІДТВОРЕННЯ ІНТЕЛЕКТУАЛЬНОГО КАПІТАЛУ - Levina, I.V. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2011)
The paper presents the conception of intellectual capital reproduction. It is based on a system approach to definition of structural relations and mechanisms of formation and accumulation of intellectual capital. It has been proved that the existence of institutional «traps» leads to ineffective reproduction of intellectual capital. The recommendations are given to increase the efficiency of accumulation of intellectual capital.